2023
DOI: 10.7759/cureus.36704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outpatient Access to the Greek Health System Considering the Constraints of the COVID-19 Pandemic

Abstract: BackgroundThe COVID-19 pandemic fundamentally changed the way healthcare is delivered in most healthcare systems around the world. It is now known that, in addition to the medical and economic impact of the pandemic on societies, there is another unmet medical need due to the difficulties and barriers that have existed and may still exist in the provision of health services at the primary care level in public hospitals. In Greece, there appears to have been a similar problem in citizens' access to health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On 11 March 2020, the World Health Organization (WHO) declared the outbreak of SARS-CoV-2 as a pandemic [1]. Individuals infected with SARS-CoV-2 developed coronavirus disease 2019 (COVID- 19), leading to elevated rates of hospitalisation and admission to intensive care units (ICUs) [2]. This new disease imposed an overwhelming burden on healthcare infrastructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On 11 March 2020, the World Health Organization (WHO) declared the outbreak of SARS-CoV-2 as a pandemic [1]. Individuals infected with SARS-CoV-2 developed coronavirus disease 2019 (COVID- 19), leading to elevated rates of hospitalisation and admission to intensive care units (ICUs) [2]. This new disease imposed an overwhelming burden on healthcare infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in difficulties both in consulting with specialists and in scheduling appointments. Half of the outpatient participants in the study reported challenges in communicating with hospitals to arrange appointments or access medical services overall [19].…”
Section: Introductionmentioning
confidence: 99%